Conscientiousness and Forgivingness: A Meta-Analysis - BALLIET, Daniel (Institutional Knowledge at Singapore Management University, 2010)
Research examining the relationship between the Big Five traits and forgivingness has focused primarily on the traits agreeableness and neuroticism. To date, there are mixed findings on the relationship between conscientiousness and forgivingness. This paper presents research and theory that predicts a positive relationship between conscientiousness and forgivingness, and in order to examine this hypothesis, conducts a quantitative review of 15 studies (n = 2285) reporting this relationship. This analysis results in a small positive effect size (r = .17). Implications and directions for future research are discussed.